Pengaruh Kompetensi, Budaya Kerja dan Komitmen Terhadap Kepuasan Kerja dan Kinerja Pegawai - Indar, SofyanHamid; Anggraini, Ayu; Junaidin, Junaidin (Jurnal Mirai Management, 2023)
This research was conducted to see how big the influence of competence, work culture and commitment to job satisfaction and employee performance. This type of research is quantitative research, which uses descriptive analysis methods and inferential statistics, namely Structural Equation Modeling (SEM) using AMOS (Analysis Of Structural Moment) software, Microsoft Excel, and SPSS software. By taking a sample using a stratified/clustered random sample (proporionated random sampling), in each Regional Government Work Unit of the Selayar Islands Regency. The results of the study indicate that competence has a negative and significant effect on employee job satisfaction and employee performance. Work culture and organizational commitment have a positive and significant effect on employee job satisfaction and employee performance. Employee job satisfaction has a positive and significant effect on employee performance. The mediating role of job satisfaction in analyzing the effect of competence on employee performance is negative and insignificant. The mediating role of job satisfaction in analyzing the influence of culture on employee performance is positive and not significant. The mediating role of job satisfaction in analyzing the effect of organizational commitment on employee performance is positive and significant. The results of this study can also be used as input for the local government of the Selayar Islands Regency in formulating policies regarding competence, work culture, organizational commitment and job satisfaction as well as employee performance in the future. Also as a reference material for future researchers. Keywords: Competence, Work Culture, Commitment, Job Satisfaction, and Employee Performance.